ESTUDO SÃ”BRE A PRECISÃƒO DE ALGUNS MÃ‰TODOS PRÃTICOS DE CONTRÃ”LE LEITEIRO - Jardim, W. R.; Peixoto, A. M.; F., S. Silveira; Gomes, F. Pimentel (REVISTA DE AGRICULTURA, 2016)
ESTUDO SÃ”BRE A PRECISÃƒO DE ALGUNS MÃ‰TODOS PRÃTICOS DE CONTRÃ”LE LEITEIRO